Exopolysaccharides composition produced by rhizobia under different carbon sources - Luque Castellane, Tereza Cristina (2007)
The objective of this work was to evaluate the effect of different carbon souces on the exopolysaccharides composition produced by Rhizobium tropici SEMIA 4077 and SEMIA 4080, and the effect of these strains inoculation on the nodulation in common bean. The carbon sources used interfered on the concentrations of the galactose and glucose of exopolysaccharides, being higher in SEMIA 4080 strain when cultivated in sucrose medium. Even though SEMIA 4080 strain produced a large quantity of exopolysaccharides in culture, there was no difference between strains regarding the number of nodules, independently of the carbon source used for inoculum preparation. However, in the parameter dry weight of nodules there was significant difference between the strains, independently of the carbon sources used for inoculum preparation.